FAKTOR KONVERSI BETA•KAROTEN SAYURAN YANG DIKERINGKAN PADA TIKUS PERCOBAAN - Almasyhuri -; Erwin Affandi (Persagi, 2006)
Background: The conversion value of -carotene to vitamin A is dependlng on the kind of foods. The ratio is about 11 : 1 for fruit and 31 : 1 for vegetable, but the conversion value of dried vegetables had not known yet. Objective: To determine the conversion value of carotene dried vegetable to vitamin A. Method: The study was conducted using 35 white mice strain KLMR (Lembaga Makanan Rakyat)